PENGARUH GAYA KEPEMIMPINAN CAMAT TERHADAP SEMANGAT KERJA BAWAHAN DI KECAMATAN PANCA LAUTANG KABUPATEN SIDENRENG RAPPANG - Muh Amin Z (PRAJA: Jurnal Ilmiah Pemerintahan, 2018)
This study aims to determine how much influence the leadership style on employee morale at the District Office Panca Lautang Sidenreng Rappang and to identify factors that affect the style of leadership at the District Office camat Panca Lautang Sidenreng Rappang. The population in this study were 33 people employees. Sampling was conducted using a sample of 33 people total resulting .Tekhnik employee data collected in this study is a literature study, observation, questionnaire, interview (interview) The collected data is then used quantitative data analysis techniques with frequency table. These results indicate that the influence of leadership style camat to employee morale at the District Office Panca Lautang Sidenreng Rappang categorized quite influential with an average of 66.52%. Hereditary factors considered influential by an average of 70.25%. Social factors influence categorized by an average of 84.75%. Factors considered influential enough talent with an average of 71.75%.